2002
DOI: 10.1046/j.1365-2044.2002.02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning to apply effective cricoid pressure using a part task trainer

Abstract: SummaryAn anatomically-correct model of a larynx inside a head and neck model was constructed so that the location, direction and amount of force applied to the neck could be measured. Fifty trained staff from three general hospitals were then asked to apply cricoid pressure on the model. None was able to state the force that should be applied (30 N), and only five (10%) actually applied cricoid pressure effectively. After training using the model, 45 (90%) applied cricoid pressure correctly (p < 0.001). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 23 publications
3
64
1
1
Order By: Relevance
“…It also supports the findings of previous work relating to the inconsistency of forces applied by different anaesthetists [2]. We would argue that the proposals put forward to the BSI regarding disposable laryngoscope blades are inadequate.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…It also supports the findings of previous work relating to the inconsistency of forces applied by different anaesthetists [2]. We would argue that the proposals put forward to the BSI regarding disposable laryngoscope blades are inadequate.…”
supporting
confidence: 87%
“…Simulation of the ultrasound appearances during CVC placement might aid the development of the necessary manual co-ordination skills without compromising patient safety. Furthermore, the experiences of part task simulation in the training of other similar clinical skills suggest that it can play an important role [2]. The main disadvantage of phantoms is the production costs and degradation of the ultrasound medium during use.…”
Section: ó 2004 Blackwell Publishing Ltdmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven randomized, controlled studies demonstrated that cricoid pressure can delay or prevent the placement of an advanced airway and that aspiration can occur despite application of pressure. 174 -180 Additional manikin studies [181][182][183][184][185][186][187][188][189][190][191][192][193][194] found training in the maneuver to be difficult for both expert and nonexpert rescuers. Neither expert nor nonexpert rescuers demonstrated mastery of the technique, and the applied pressure was frequently inconsistent and outside of effective limits.…”
Section: Cricoid Pressurementioning
confidence: 99%